MANAGEMENT OF THE DELIVERY ROUTE IN PREMATURE PLACENTAL ABRUPTION - Baldoni, Luiza Dias; Araújo, Clayseane Nunes; Oliveira, Amanda dos Santos; Grasso, Isabela Vitória; Costa, Julia Marjorie Pires (Seven Editora, 2026)
Introduction: Premature Placental Abruption (PPA) is considered an obstetric emergency. This is because it involves the partial or total separation of the placenta, a temporary organ that arises during pregnancy to nourish and oxygenate the fetus. PPA usually occurs after the 20th week of pregnancy and can be caused by multiple factors: high blood pressure, abdominal trauma, use of chemical substances, premature rupture of membranes, among others. It is one of the most critical conditions in obstetrics, as it is associated with high rates of perinatal mortality. Method: This research constitutes a narrative literature review. Data retrieval was performed in the PubMed database using the descriptor "Premature Placental Abruption," integrated according to the Medical Subject Headings (MeSH) terminology. The selection included studies published between 2021 and 2025, with full text available in English or Portuguese, addressing the clinical and surgical management of PPA. Results and Discussion: Early identification of the signs and symptoms of this condition is extremely important for choosing the delivery method. It is necessary to assess the health status of both mother and baby before intervening. However, emergency cesarean section is generally the gold standard due to the rapid deterioration of the maternal and fetal clinical condition. It is worth noting, however, that the decision must be made with great caution and safety, because although cesarean section increases the chances of saving lives, it also poses risks like any surgical procedure: hemorrhage, infection, and organ perforation. As for vaginal delivery, this is only indicated when the pregnancy is at term or periterm, there are no signs of complications, or placental abruption is in its early stages. Another possibility is when fetal death has already occurred due to severe placental abruption. In these situations, labor is induced. Conclusion: Early attention to risk factors allows the pregnant woman to be monitored more closely or even undergo high-risk prenatal care. Ultrasound examination is fundamental for identifying uterine abnormalities, fibroids, twin pregnancies, and subchorionic hematomas—aspects that raise concerns about placental abruption. Therefore, healthcare professionals attending to pregnant women, whether in primary care or hospital settings, should frequently monitor the gestational trajectory in order to intervene when the pregnancy no longer offers benefits.